Peningkatan Keterampilan Ibu Rumah Tangga Desa Glagaharum melalui Pelatihan Desain Menjadi Pakaian Berbasis Entrepreneurship - Lainardy, Jesslyn Eunice; Balqis, Raissa Ariella Shafa; Tjioe, Vincentia Jennifer Evelyn; Sitepu, Sri Nathasya Br (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Glagaharum Village in Sidoarjo has untapped economic potential. Some residents earn below the minimum wage. Housewives have sewing skills but are less able to change product designs. Limited knowledge of fashion design and business is a major obstacle. The "Kampung Jahit Arumpreneur" program aims to empower housewives by improving sewing and design skills. The implementation method is in the form of mentoring to improve knowledge and skills for participants to increase fashion production capacity. Mentoring bridges the gap in potential, skills to produce high-quality Muslim clothing and improve the village economy. Mentoring is an initiative to support SDG 4 by providing quality education and expanding participants' understanding of the fashion industry. The results of the mentoring activities for participants are in the form of increasing entrepreneurial knowledge and application skills (making patterns, prototypes and identifying material quality). The results of the second mentoring create participants with economic independence.